Penguatan Pola Asuh Demokratis di TK Pertiwi 34 Patemon - Amelindha, Nabilla Fasya; Noor, Zaima Aulia; Adiningrum, Aisha Inastya; Septiana, Laily Wakhidah; Rohmah, Naili; S, Sugiana (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Parenting is very important for children because it determines how the child's journey and destiny will be in the future so that all behavior, actions, values, morals, rules, and beliefs held by children are influenced by the role of parents in educating. However, this is different in the real world, many parents are not aware of their role as figures who are dependent on children so that they become anarchic, destructive figures, and carry out other negative behaviors. The problem of parenting also occurs in Pertiwi 34 Patemon Kindergarten where many parents lack knowledge related to parenting so that many parents unknowingly apply parenting patterns that are not good for child development. Community service is carried out in the form of Socialization through Power Point media. The presentation of material on "Democratic Parenting" was presented by the Community Service Team. After the presentation, the guardians asked questions related to the material "Democratic Parenting" to the community service team. This socialization activity was carried out on Wednesday, March 19, 2025. The activity was carried out at Pertiwi 34 Patemon Kindergarten which was attended by 54 guardians. Parents participated in the activity enthusiastically and paid attention during the activity.